PELINDUNGAN HUKUM TERHADAP PRODUK PERTANIAN YANG MEMILIKI INDIKASI GEOGRAFIS DI KABUPATEN HUMBAHAS - BASARIA TINAMBUNAN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. Jelly Leviza, SH, MHum3. Dr. T. Keizerina Devi A, SH, CN, MHumGeographical indication is the national economic potency which give commercial value-added on products due to their originality and limitation which cannot be produced in other places. The agricultural product which has been registered as geographical indication is Lintong Sumatera Arabica coffee, while the other products which have not been registered are incense, patchouli, and andaliman. That some criteria of agricultural products which have geographical tendency and have the potency to be registered according to Law No. 20/2016 are natural resources, human resources, of both of them which give reputation, quality, and certain characteristics in the products. Some obstacles are lack of information from the government, lack of sense of justice, lack of people’s understanding, and long duration of the process of HKI registration. The role of the local government in registering agricultural products potential for geographical indication in Humbahas Regency is not focused and serious.Keywords: Legal Protection, Geographical Indication